Cost-effectiveness of Cabotegravir Long-Acting for HIV Pre-exposure Prophylaxis in the United States - Brogan, Anita J.; Davis, Ashley E.; Mellott, Claire E.; Fraysse, Jeremy; Metzner, Aimee A.; Oglesby, Alan K. (PharmacoEconomics, 2024)
Objective Cabotegravir long-acting (CAB–LA) administered every 2 months was approved in the USA as pre-exposure prophylaxis (PrEP) for individuals at risk of acquiring human immunodeficiency virus (HIV)-1 infection based on the HIV Prevention Trials Network (HPTN) 083 and HPTN 084 clinical trials, which demonstrated superior reduction in HIV-1 acquisition compared with daily oral emtricitabine/tenofovir disoproxil fumarate (FTC/TDF) in men who have sex with men (MSM), transgender women (TGW), and cisgender women. A decision-analytic model was developed to assess the lifetime cost-effectiveness of initiating CAB–LA versus generic oral FTC/TDF for HIV PrEP in the USA from a healthcare sector perspective. Methods PrEP-eligible adults entered the Markov model receiving CAB–LA or FTC/TDF and could continue initial PrEP, transition to a second PrEP option, or discontinue PrEP over time. Efficacy was taken from the HPTN 083 and HPTN 084 clinical trials. Individuals who acquired HIV-1 infection incurred lifetime HIV-related costs, could transmit HIV onwards, and could develop PrEP-related resistance mutations. Input parameter values were obtained from public and published sources. Model outcomes were discounted at 3%. Results The model estimated that the CAB–LA pathway prevented 4.5 more primary and secondary HIV-1 infections per 100 PrEP users than the oral PrEP pathway, which yielded 0.2 fewer quality-adjusted life-years (QALYs) lost per person. Additional per-person lifetime costs were $9476 (2022 US dollars), resulting in an incremental cost-effectiveness ratio of $46,843 per QALY gained. Results remained consistent in sensitivity and scenario analyses, including in underserved populations with low oral PrEP usage. Conclusions Our analysis suggests that initiating CAB–LA for PrEP is cost-effective versus generic daily oral FTC/TDF for individuals at risk of acquiring HIV-1 infection.